Gender equality principle in the convention on the elimination of all forms of discrimination againt women (CEDAW) : a critical analysis from the Qur'anic perspective - Nurul Syuhada Ismail (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
The study examines the Convention on the Elimination of all Forms of ‎Discrimination against Women (CEDAW) approaches to gender equality principles ‎in comparison with the Qur'anic perspective. The issue rises within CEDAW's article ‎implementation where the article is regulated by disregarding culture, custom and ‎religion practices. As a result, Muslim countries which ratified and acceded to ‎CEDAW have to reserve certain articles such as the reservation of Article 16 due to ‎its contradiction with principles and approaches of the Qur'an and Sunnah. Therefore, ‎the study brief on CEDAW's background, examines the Western and Islamic concept ‎of gender equality and analyses the contradiction in the principles of gender ‎approaches between CEDAW and the Qur'anic provisions in order to expose the ‎issue of developing the concept of equality extensively. Thus, a qualitative ‎methodology was selected as the research methodology for analysing the issue. The ‎methodology consists of the critical analysis method where the study analyses 16 ‎articles of gender equality to grasp the understanding of the Convention principles by ‎dividing them into three perspectives: marital aspect, inheritance and property and ‎reproductive rights. The study has also adopted the comparative analysis method to ‎compare between gender approaches by CEDAW and the Qur'anic provisions. In ‎conclusion, the study will exhibit the results of the comparison where standardisation ‎of gender equality approaches by CEDAW needs to be critically reviewed ‎considering different major components of human life. These components have been ‎overlooked and the study concludes that comprehensive concept and approaches of ‎gender by the Qur'an removes any misconception about Islam in regards to women's ‎rights.‎